Neurobehavioural evaluation of Venezuelan workers exposed to inorganic lead. Issue 6 (June 1995) - Maizlish, N A; Parra, G; Feo, O
Abstract : OBJECTIVES–To assess neurobehavioural effects of low exposure to lead, 43 workers from a lead smelter and 45 workers from a glass factory were evaluated with the World Health Organisation neurobehavioural core test battery (NCTB) in a cross sectional study. METHODS–The NCTB comprises a questionnaire and seven tests that measure simple reaction time, short-term memory (digit span, Benton), mood (profile of mood states), eye-hand coordination (Santa Ana pegboard, pursuit aiming II), and perceptual speed (digit-symbol). RESULTS–Smelter workers were employed on average for four years, and had a mean blood lead concentration of 2.0 mumol/l (42 micrograms/dl). Glass factory workers had a mean of 0.72 mumol/l (15 micrograms/dl). Historical blood lead concentrations were used to classify exposure based on current, peak, and time weighted average. Although the exposed workers performed less well than the non-exposed in 10 of 14 response variables, only profile of mood states tension-anxiety, hostility, and depression mood scales showed a significantly poorer dose-response relation with blood lead concentration in multiple linear regression models that included age, education, and alcohol intake as covariates. The frequency of symptoms of anger, depression, fatigue, and joint pain were also significantly increased in the exposed group. CONCLUSION–This study is consistent with the larger body of neurobehavioural research of low occupational exposure to lead. The small effects found in this study occurred at blood lead concentrations slightly lower than those reported in several previous studies.